CONVEYOR-TYPE SMALL HYDROPOWER PLANT FOR SHALLOW RIVER WATERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper deals with the development of a small conveyor-type hydropower plant intended for operation in shallow river waters without construction of a dam. The proposed design offers a closed-shaped flattened conveyor equipped with flat-shaped blades. The conveyor is oriented perpendicular to the fluid flow. Several identical flat blades interacting with fluid flow are mounted on conveyor belt and move together with the belt in one straight line direction. Then after turning in the reversing mechanism, blades move in the opposite direction. The conveyor system has a built-in energy generator which drive shaft is connected with one of the reversing ends of the plant. Conveyor belt system dynamics analysis is performed on the base of equivalent model with one degree of freedom. The interaction of a moving conveyor flat blade in translation motion with fluid flow is studied by computer simulation with program Mathcad using a superposition principle. In accordance with this approach, a fast-chaotic motion of fluid particles (Brownian motion) is separated from the slow-directed flow motion, with the given average velocity. Optimization of system parameters (blade orientation angle to fluid flow, interaction constants of the braking generator) is performed, using a generated power as criterion. Simulation results confirm the serviceability and operational efficiency of the proposed hydropower plant in shallow river waters.